Quebec City's Literary Heritage : A Bibliography - Donovan, Patrick (Literary & Historical Society of Quebebc, 2007)
The Literary and Historical Society of Quebec (LHSQ), founded in 1824, has a mandate to foster English-language culture in the Quebec City region and to share its diverse heritage. Literature is a vital element in this heritage, and the LHSQ has taken on a project to celebrate Quebec City’s English-language literary heritage. The first step of this project is to generate an accessible knowledge base, or bibliography. This tool will have several repercussions: book purchases for the LHSQ’s library, written articles to promote these books, and the hosting of literary events in 2007 and 2008. This project is financed by the Department of Canadian Heritage as part of the Development of Official-Language Communities Program - Community Life component.

History of the Coasters Association 1988-2007 - Maurice, Cornella (Coasters Association, 2007)

Society Pages - Morrin Centre (2007)

Society Pages - Morrin Centre (2007)

Society Pages - Morrin Centre (2007)

Society Pages - Morrin Centre (2007)